2018
DOI: 10.1016/j.jbiomech.2017.12.015
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of the supraspinatus muscle at sub-maximal contractions

Abstract: During maximum effort, the supraspinatus muscle contributes approximately 50% of the torque need to elevate the arm, but this has not been examined at sub-maximal levels. The purpose of this study was to determine the contribution of the supraspinatus muscle to shoulder elevation at sub-maximal levels. Seven healthy subjects (four males, three females) performed isometric ramp contractions at the shoulder. Middle deltoid electromyography (EMG) and force applied at the wrist were collected before and after a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
4
0
3
Order By: Relevance
“…The rotator cuff comprises the subscapularis, supraspinatus, infraspinatus, and teres minor tendons; among these, the supraspinatus tendon is the most vulnerable. The supraspinatus tendon abducts the upper arm following muscle contraction, and the stress is relatively concentrated in the central area of the tendon; thus, a supraspinatus injury is related to the mechanical function and anatomy of the shoulder joint [ 9 ]. The supraspinatus tendon can be partially torn due to degeneration, tension, internal impact, and other factors.…”
Section: Discussionmentioning
confidence: 99%
“…The rotator cuff comprises the subscapularis, supraspinatus, infraspinatus, and teres minor tendons; among these, the supraspinatus tendon is the most vulnerable. The supraspinatus tendon abducts the upper arm following muscle contraction, and the stress is relatively concentrated in the central area of the tendon; thus, a supraspinatus injury is related to the mechanical function and anatomy of the shoulder joint [ 9 ]. The supraspinatus tendon can be partially torn due to degeneration, tension, internal impact, and other factors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Park et al suggested that the fracture should be repaired if the displacement is more than 5 mm in young active patients, while fractures with 3 mm of displacement should be reduced in heavy laborers and athletes who are involved in overhead activity [ 30 ]. Our results showed that two-screw construct augmented with a cerclage wire had less than 3 mm displacement under 200 N load which was strong enough to bear rehabilitation interventions [ 31 ]. The two-screw construct augmented with a cerclage wire, average failure load more than 400 N, is expected to tolerate the maximal load from the supraspinatus of ~ 302 N [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Так, основною функцією ПОМ визначено забезпечення зовнішньої ротації плеча [14]. НОМ у свою чергу здійснює контрвплив на дельтоподібний м'яз (ДМ), не дозволяючи передній порції останнього як зміщувати голівку плечової кістки догори, стабілізуючи її в гленоїдальній западині [14,21], й проводити згинання плеча [14], так і максимально реалізовувати потенціал середньої порції ДМ у провадженні відведення [21].…”
Section: обговоренняunclassified